DIETRY HABITS OF SHORT TAILED MOLE RAT (Nesokia indica) IN AGRO-ECOSYSTEM OF POTHWAR PLATEAU, PAKISTAN - A. Saman; T. Mahmood; A. Razaq; N. Munawar; A. Baig; F. Akrim; M. Farooq (Journal of Animal and Plant Sciences, 2022)
Rodents are important component of biodiversity of the agricultural land being prey species to snakes, raptor birds, as well as mongooses. However, these have been identified as destructive pests of agricultural crops at the same time. In the current study, we investigated the dietary habits of short tailed mole rat (Nesokia indica) inhabiting croplands of Pothwar Plateau. The rodent specimens were trapped from four selected sampling sites (one each from district; Rawalpindi, Attock, Jhelum, and Chakwal), of the Plateau, from groundnut and wheat fields, from the fallow lands inside the crop fields and on the field boundaries, by using both kill and live baited traps. The stomach contents of the captured specimens were analyzed using micro histology technique. Results revealed higher trapping success during cropping season of wheat (n= 18), followed by peanut (n= 12) while during non-cropping season capturing success was low and specimens were mostly caught from field boundaries. The rodent species mostly consumed wheat and groundnut during their cropping seasons. Simultaneously, it also consumed fodder crops (millet, barley and sorghum), along with supplementation with varying proportions of wild vegetation. The proportion of wild vegetation in the total diet of the rodent species varied from approximately 20% to 43% (by volume) and a higher consumption of wild vegetation during spring and summer seasons was noticeable. The study concludes that although short tailed mole rat consumed cultivated crops mainly, yet wild vegetation of the study area in significant proportion served as its staple food sustaining it throughout the year, especially during the non-cropping seasons of wheat and groundnut crops.
Keywords: Short tailed mole rat; dietary habits; stomach contents; Pothwar; cropping and non-cropping seasons; wild vegetation